2011
DOI: 10.1007/s10571-011-9656-7
|View full text |Cite
|
Sign up to set email alerts
|

Lower Frequency of Antidepressant Use in Patients on Renin-Angiotensin-Aldosterone System Modifying Medications

Abstract: Both hypertension and depression are common disorders which may both involve components of the hypothalamic-pituitary-adrenal axis system and the Renin-Angiotensin-Aldosterone System (RAAS). These observations, coupled with growing evidence that RAAS-active drugs may have anti-depressant properties prompted us to study the frequency of anti-depressant medication usage in the patients receiving RAAS-active agents. A chart review was performed on 378 patients who were seen during a 3-month period in a primary ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 23 publications
(22 reference statements)
1
22
0
Order By: Relevance
“…ARBs have been reported to improve mood and the regulation of the HPA axis in diabetic patients (Pavlatou et al 2008). Depressed patients medicated with ARBs to treat co-morbid hypertension improve their response to and require lower doses of antidepressants to achieve therapeutic efficacy (Nasr et al 2011), and a similar finding was earlier reported in patients treated with inhibitors of Angiotensin II formation the Angiotensin Converting Enzyme inhibitors (ACEI) (Braszko et al 2003; Hertzman et al 2005). …”
Section: Introductionsupporting
confidence: 66%
“…ARBs have been reported to improve mood and the regulation of the HPA axis in diabetic patients (Pavlatou et al 2008). Depressed patients medicated with ARBs to treat co-morbid hypertension improve their response to and require lower doses of antidepressants to achieve therapeutic efficacy (Nasr et al 2011), and a similar finding was earlier reported in patients treated with inhibitors of Angiotensin II formation the Angiotensin Converting Enzyme inhibitors (ACEI) (Braszko et al 2003; Hertzman et al 2005). …”
Section: Introductionsupporting
confidence: 66%
“…These effects occur not only in hypertensive subjects, but also in normotensive patients and in those affected with diabetes [5,179,222229] (Table 1). This indicates that there appears to be a good correlation between the anti-stress, anti-anxiety, anti-depressant, anti-inflammatory and cerebrovascular-protective effects of ARBs, as revealed in rodent models and observational studies in humans.…”
Section: Translational Potential Of Arbs For the Treatment Of Brain Dmentioning
confidence: 99%
“…Although it has been established that AngII‐mediated AT 1 R signalling results in the activation of proinflammatory pathways in numerous cell types, including cardiac myocytes, vascular endothelial cells and neurons, the role of the RAS in microglial cell function is not as well understood. In terms of disorders of the CNS, blockade of the AT 1 R has been found to be beneficial in AD, in which disease progression was slowed in patients treated with an ARB, and depression, in which patients taking an ARB required a lower dose of antidepressant to achieve an efficacious response . These clinical findings are supported by animal studies showing reduced neuronal damage in animals treated with an ARB following experimentally induced AD, PD, traumatic head injury and stroke .…”
Section: Microglia and The Rasmentioning
confidence: 90%